1997
DOI: 10.1152/ajpregu.1997.272.1.r243
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the anorexia of aging: gastrointestinal transit and hunger in healthy elderly vs. young adults

Abstract: Animal studies suggest that aging is associated with anorexia and disordered gastrointestinal transit. To determine whether there is a relationship between the effects of aging on appetite and gastrointestinal transit in humans, 19 young (age 23-50 yr) and 14 elderly (age 70-84 yr) normal volunteers underwent measurements of 1) desire to eat, hunger, and fullness (visual analog scales); 2) gastric emptying (scintigraphy); 3) orocecal transit (breath hydrogen); 4) total gut transit (radiopaque markers); and 5) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
167
1
6

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(182 citation statements)
references
References 0 publications
8
167
1
6
Order By: Relevance
“…Indeed, Clarkston et al [12] demonstrated that gastric emptying of both liquids and solids is delayed by ~26% and 30%, respectively, in old compared to young subjects. The gastric emptying rate of a liquid is linearly related to the energy density of the liquid [17], with more energy dense liquids emptying from the stomach more slowly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, Clarkston et al [12] demonstrated that gastric emptying of both liquids and solids is delayed by ~26% and 30%, respectively, in old compared to young subjects. The gastric emptying rate of a liquid is linearly related to the energy density of the liquid [17], with more energy dense liquids emptying from the stomach more slowly.…”
Section: Discussionmentioning
confidence: 99%
“…The provision of water 30 minutes before a meal allows time for the water to empty from the stomach, which will reduce the amount of gastric distention present at the onset of feeding. Given that the rate of gastric emptying for liquid meals is slower in older vs. younger adults [12], reducing the time between preload ingestion and feeding in young adults might increase gastric distention during feeding and reduce ad-libitum food intake.…”
Section: Introductionmentioning
confidence: 99%
“…Gastric emptying is delayed after meals in older subjects, increasing satiation. 47 Older individuals also have a decreased olfactory sense and increased taste threshold 48,49 and may experience less intense hunger signals; 29,31,47 therefore, they may be less sensitive to stimulation by the presence of food than younger persons. However, differences with age in hormonal mechanisms that regulate sensitivity to dietary factors are uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…2), because that is typical immediately after meal intake rather than at fasting, when pH is below 2.0 (16,50) and thereby avoids a total loss of culturable bacteria. Second, the Analog models the acid cycle exposure time according to stomach acid concentrations of young healthy adults with an average time of ϳ120 min for 50% of their stomach contents to empty (12). Finally, only very gradual acidification with human physiological pH concentration of cephalic phase parietal cell secretion (25) and alkalization with shaking achieves similarity to human gastric conditions and yields successful survival and tractable measurements of fitness.…”
Section: Experimental Evolutionary Adaptation To Environmental Phmentioning
confidence: 99%